United Republic of Tanzania : Staff Report for the 2016 Article IV Consultation and Fourth Review Under the Policy Support Instrument-Press Release; Staff Report; and Statement by the Executive Director for The United Republic of Tanzania. (IMF Staff Country Reports; Country Report ;, 2016)
This 2016 Article IV Consultation highlights that growth in Tanzania has remained strong and inflation moderate during the past two years. Real GDP grew by 7 percent in 2015, with activity particularly buoyant in the construction, communication, finance, and transportation sectors. Inflation remained in single digits throughout 2015, averaging 5.6 percent, despite the significant exchange rate depreciation in the first half of 2015. Inflation in April 2016 was 5.1 percent, close to the authorities' target of 5 percent. The banking system appears sound overall, but there is wide variation within the system. The level of financial development has improved in recent years, though at a gradual pace.